(untitled) (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2022)
This study aims to optimize the temperature and time of the delignification process to isolate cellulose from corn cobs. The research was carried out in stages, namely preparing corn cob powder samples and the delignification process. Statistical regression modeling and optimization of the temperature and time of the delignification process used the response surface (RSM) methodology. Central Composite Design (CCD) was used for experimental design and analysis of the effect of temperature and time of the delignification process on lignin, cellulose, hemicellulose, and fiber yields. The optimum process conditions were determined using the desirability method. The analysis of the diversity of the quadratic polynomial model shows that the temperature and time of the deligninification process significantly affect changes in the characteristics of lignin, cellulose, hemicellulose, and fiber yields. The optimal condition of the corncob fiber delignification process was obtained at a temperature of 100.38? for 79.17 minutes. It produced the characteristics of delignified fiber with lignin, cellulose, hemicellulose, and yields of 6.47%, 73.73%, 5, respectively. 39% and 57.76% w/w. The optimization model is valid with a desirability value of 0.71. Thus, the temperature and time optimization model of the delignification process can be applied in real conditions to produce delignified corncob fiber with optimum characteristics.